ANALISIS KETIMPANGAN PENDAPATAN PETANI PADI DI DESA JOGODALU KECAMATAN BENJENG KABUPATEN GRESIK - Yudhistira, Andhika; Amir, Indra Tjahaja; Hidayat, Syarif Imam (Berkala Ilmiah AGRIDEVINA, 2020)
The high rice production in Gresik Regency is not comparable with the level of welfare of rice farmers. The inequality of income distribution of rice farmers has resulted in income disparities between rice farmers. The problem of income inequality is one indicator in seeing the level of community welfare. This study aims to identify the diversity of sources of income of rice farmers, analyze rice farming income and its contribution to the total household income of rice farmers and analyze the income inequality of rice farmers in Jogodalu Village, Benjeng District, Gresik Regency. The research method for determining the area is done intentionally. Whereas for sampling, the method used was purposive sampling with the characteristics of rice farmers with rice farming income and other income outside of rice farming. the number of samples taken in this study were 42 samples. The analysis used was descriptive qualitative analysis, analysis of income and income of rice farmers and analysis of the Gini Ratio (supplemented by Lorenz Curve). The results showed that the source of income of rice farmers outside rice farming was quite diverse. Rice farming income has a total average income of Rp. 146,707,377 with an average contribution of farm income to total household income of 52%. The income inequality of rice farmers in Jogodalu Village was obtained by the Gini Ratio index of 0.20 and was in the low category. DOI : https://doi.org/10.33005/adv.v9i1.2208